2000
DOI: 10.1093/intjepid/29.3.456
|View full text |Cite
|
Sign up to set email alerts
|

How accurately are height, weight and leg length reported by the elderly, and how closely are they related to measurements recorded in childhood?

Abstract: Self-reported measures of height and weight may be used in studies of the elderly although systematic reporting errors may bias effect estimates. As overweight individuals tend to under-report and the short and underweight tend to over-report, studies investigating associations of disease with height and weight using self-reported measures will underestimate effects. The weak associations between childhood and adult BMI indicate that associations between childhood adiposity and adult cardiovascular disease fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
70
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 19 publications
7
70
1
Order By: Relevance
“…The results of our study are generally consistent with previous studies conducted in Western countries, some of which had the same age subgroups as our study population. [1][2][3][4][5][6][7][8][9] In previous studies, self-reported height, weight, and BMI were similarly strongly correlated with measured height, weight, and BMI, and the correlations were usually more than 0.90.…”
Section: Yong and Y Saitomentioning
confidence: 99%
See 4 more Smart Citations
“…The results of our study are generally consistent with previous studies conducted in Western countries, some of which had the same age subgroups as our study population. [1][2][3][4][5][6][7][8][9] In previous studies, self-reported height, weight, and BMI were similarly strongly correlated with measured height, weight, and BMI, and the correlations were usually more than 0.90.…”
Section: Yong and Y Saitomentioning
confidence: 99%
“…Likewise, weight underreporting was also documented, with women and heavier people more likely to underreport their weight. [1][2][3][4][5][6][7] Weight underreporting in previous studies ranged on average from 0.54-0.76 kg for men and 0.85-2.50 kg for women. This study had similar findings for women, with underreporting falling at the lower end of the range, but the discrepancies were larger for men.…”
Section: Yong and Y Saitomentioning
confidence: 99%
See 3 more Smart Citations